Insulin Resistance Promotes the Formation of Aortic Dissection by Inducing the Phenotypic Switch of Vascular Smooth Muscle Cells - Zheng, Hui; Qiu, Zhihuang; Chai, Tianci; He, Jian; Zhang, Yuling; Wang, Chaoyun; Ye, Jianqiang; Wu, Xiaohui; Li, Yumei; Zhang, Li; Chen, Liangwan (Frontiers in Cardiovascular Medicine, 2022)
Background: Insulin resistance (IR) plays a key role in the development of type 2 diabetes mellitus(T2DM) and is one of the most important characteristics of it. Previous studies have shown that IR and T2DM were independent risk factor for a variety of cardiovascular and cerebrovascular diseases. However, there are few studies on the relationship between IR and aortic dissection (AD). This research is dedicated to finding evidence that IR stimulates the occurrence of AD. Methods: Through statistical analysis the proportion of glycosylated hemoglobin (HbA1c) abnormalities (HbA1c>5.7) in people with acute thoracic aortic dissection (ATAD) and comparing the difference of mRNA and protein expression of GluT1 in thoracic aortic between normal and ATAD, to find the evidence that IR is a causative factor of AD. The mouse model of IR and AD, the IR model of HA-VSMC were established, RT-PCR and Western blotting were used to study the mRNA and protein expression; H&E, Masson and elastic fiber staining and immunofluorescence were used to study the morphological structure. Results: The proportion of HbA1c abnormalities in patients with ATAD was 59.37%, and the mRNA and protein expression of GluT1 were significantly lower than that of the normal. Fasting glucose concentration (FGC), Serum Insulin concentration (SIC) and the homeostasis model assessment of insulin resistance (HOMA-IR) of mice were obvious risen in the high-fat diet group, the protein expression of Glut1 and GluT4 were reduced, indicate that the mouse IR model was successfully established. The incidence of AD was different between the two groups (IR:13/14, Ctrl:6/14), and the protein expression of MMP2, MMP9 and OPN were up-regulated, SM22 and α-SMA were down-regulated in model mice. The expression of mRNA and protein of GluT1 and SM22 in HA-VSMCs with IR were reduced, and which of OPN were raised. Conclusions: Combining the results of clinical, mouse models and cell experiments show that IR induced the phenotypic switching of VSMC from contractile to synthetic, which contributes to the occurrence of AD. It provides a basis for further research on the specific mechanism of IR result in AD and a new idea for the prevention and treatment of AD.